REACHING THE MILLENNIAL GENERATION THROUGH DA'WAH ON SOCIAL MEDIA: MENJANGKAU GENERASI MILENIAL MELALUI DAKWAH DI MEDIA SOSIAL - Agus, Agusman (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2023)
Millennials are a significant demographic group in this digital age. They are active influential users of social media, and therefore, understanding how to reach them through these platforms is important in the context of da'wah and Islamic message delivery. This article examines various strategies that can be used by those who are committed to da'wah to reach and interact with millennials through social media. The author analyzes the role of social media in spreading Islamic values, inviting discussion, and building strong communities. In addition, this article also discusses certain issues that need to be considered in interacting with millennials, such as authenticity, relevant content, and attractive visual aesthetics. By providing practical guidance, this article aims to help da'wah disseminators to be effective in reaching the millennial generation and have a positive impact in carrying out the mission of delivering Islamic messages in this digital era